M-Health Research Trends For Patients With Chronic illness : A Bibliometric Analysis - Hanardi, Dwi Yuliangsih Putri; Rochmawati, Erna (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Digital technology in the health sector including the m-health applications that have been widely used by health care systems. However, little is known on the research trend of the use of m-health for patients with chronic illness. The review aimed  to explore the development and trend of research that investigates the use of m-health in  patients with chronic illness. A bibliometric analysis was conducted.  Keywords related to m-health, and chronic illness, hypertension, diabetes mellitus, and COPD were used to search available literatures in SCOPUS. Boolean phrase AND and OR was used to combine the keywords. Any studies published from 2017 until 2022  were included.  An analysis conducted on 1717 original articles and reviews revealed that the countries that produce the most articles in this field are Taiwan, the United States, and followed by Australia. Network analysis based on keyword cooccurrence reveals three main keyword types namely: patient, telehealth and quality of life. The results of the bibliometric analysis show an increasing trend of publications and users of m-health technology from 2017 to 2022 for patients with chronic diseases. This explains that m-health technology for patients with chronic diseases is used as a form of health service to patients in promoting health, providing information, preventing the effects of further disease, treating, and managing chronic diseases at low cost and easily accessible.